Do warning graphics deter smoker from buying cigarette packs : a case study in Vietnam / Phuong Duy Nguyen and Yen Dan Tong - Nguyen, Phuong Duy; Tong, Yen Dan (Universiti Teknologi MARA, Shah Alam, 2019)
Under a burden of non-communicable diseases associated with smoking, Vietnamese people are facing the socio-economic and health-related problems. In this context, many policy instruments have been studied and applied into the task of preventing and warning about the harm of tabacco use. In line with that, this study aims to identify which information is potential to smokers to quit smoking. By using choice experiment method, a survey was carried out on 120 adult smokers in Can Tho City, Vietnam. The findings from this study indicated that all included attributes were significant in exposing the risks of cigarette smoke. Specifically, health warning graphics (i.e., the image of lung damage and damaged teeth), risk information and smoking ban in public places, and price were the effective vehicles. Surprisingly, under the lens of economics, this research found that the inefficiency in controlling smuggled tobacco is a serious problem in Vietnam, especially in its southern area. Apart from the budget deficit, this could pose a threat to the ability to conduct tobacco control policies for long-term in Vietnam.